Pottery craft development: Upgrading the traditional combustion management patterns for product quality and aesthetics in Pagelaran Village, Malang - Desti Nur Aini; Agung Winarno; Arsadi Arsadi; Norlida Hanim Mohd Salleh (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2023)
This study examines the process of improving the quality of pottery products from Pagelaran village in Malang mainly by improving the traditional combustion process. The traditional pottery craftsmen in this area have faced issues with both the aesthetic values and quality standard of their products, even having defective products due to poor processes. Despite these challenges, pottery craft in Pagelaran is considered a cultural heritage that has contributed to the welfare of craftsmen and the local community, as well as the preservation of local wisdom. To improve the quality of their products, the craftsmen in Pagelaran have focused on the way they use tools and materials, the technical production process by linking technology and the environment, the method used, and the effect on future environmental changes. This study employs a descriptive qualitative and action research, which involves the craftsmen community in Kampung Edukasi Wisata. Data is collected through observation and in-depth interviews and analyzed using the 6P simultaneous stages technique proposed by Winarno and Robfiah (2020). The findings of the study show that while the tools and materials used in the pottery production are still traditional, the pottery of Pagelaran is leading to innovative aesthetic products. Pottery production activities have an impact on the physical environment, requiring technology, methods, and cultural impact in the exploitation of the environment under the cultural ecology perspective. Despite the traditional production process, it has been integrated with user demands so that the quality of the product is improved through the standardization of the combustion process, product decoration, and additional touches of aesthetic values on the products. Overall, this study provides insights into how traditional craftsmen can improve their product quality through a focus on both the technical production process and cultural impact.Keywords: aesthetic innovation, combustion process, pottery, PagelaranPengembangan kerajinan gerabah: Peningkatan pola pengelolaan pembakaran tradisional untuk mutu dan estetika produk di Desa Pagelaran, MalangPenelitian ini mengkaji proses peningkatan kualitas produk gerabah di desa Pagelaran Malang terutama dengan perbaikan proses pembakaran tradisional. Pengrajin gerabah tradisional di daerah ini menghadapi kendala baik dari segi nilai estetika maupun standar kualitas produknya, bahkan produknya seringkali cacat karena proses yang kurang baik. Terlepas dari tantangan tersebut, kerajinan gerabah di Pagelaran dianggap sebagai warisan budaya yang berkontribusi terhadap kesejahteraan pengrajin dan masyarakat setempat, serta pelestarian kearifan lokal. Untuk meningkatkan kualitas produknya, para pengrajin di Pagelaran menitikberatkan pada cara penggunaan alat dan bahan, teknis proses produksi dengan menghubungkan teknologi dan lingkungan, metode yang digunakan, dan pengaruh terhadap perubahan lingkungan di masa depan. Penelitian ini menggunakan metode deskriptif kualitatif dan action research yang melibatkan komunitas pengrajin di Kampung Edukasi Wisata. Data dikumpulkan melalui observasi dan wawancara mendalam serta dianalisis menggunakan teknik tahapan simultan 6P yang dikemukakan oleh Winarno dan Robfiah (2020). Hasil penelitian menunjukkan bahwa meskipun alat dan bahan yang digunakan dalam pembuatan gerabah masih tradisional, namun gerabah Pagelaran mengarah pada produk estetika yang inovatif. Kegiatan produksi gerabah berdampak pada lingkungan fisik, membutuhkan teknologi, metode, dan dampak budaya dalam pemanfaatan lingkungan dalam perspektif ekologi budaya. Meskipun proses produksinya tradisional, namun telah terintegrasi dengan kebutuhan pengguna sehingga kualitas produk ditingkatkan melalui standarisasi proses pembakaran, dekorasi produk, dan tambahan sentuhan nilai estetika pada produk. Secara keseluruhan, penelitian ini memberikan wawasan tentang bagaimana pengrajin tradisional dapat meningkatkan kualitas produk mereka melalui fokus pada proses produksi teknis dan dampak budaya.Kata Kunci: estetika, inovasi, proses pembakaran, gerabah, Pagelaran